Effects of Repeatability and Heritability Growth Traits on Indigenous Guinea Pigs in Nigeria - Afodu, Osagie (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
This study focused on the genetic parameter (heritability and repeatability) estimates of growth traits of indigenous guinea pig in Nigeria. The repeatability and heritability estimates of live body weight at birth, pre, and post weaning phases of indigenous guinea pig was measured. A total of 197 indigenous growing guinea pigs, progeny of 6 sires and 18 dams was selected and raised at the Babcock University Animal holding facilities, Ilishan Remo. They were individually housed in separate labelled plastic cages. Data collected for birth weight, pre, and post weaning weight were used to evaluate the descriptive statistic, repeatability and heritability estimate using Restricted maximum likelihood (REML) of SAS software. The mean values of the live body weight revealed a consistent increase from 76.510g (birth weight) and 83.728 – 241.679 g pre-weaning (week 1-7) weight and 265.600 – 330.884 post-weaning (week 8 – 13) weight in female while the male growing guinea pig had 76.510 g (birth weight to 83.677 – 241.679 g (pre-weaning (week 1-7) weight and 265.600 – 330.986 post-weaning (week 8 – 13) weight. Birth weight recorded a high estimate of repeatability for growing female guinea pig whereas, the anchored week, 4th week of age for pre-weaning phase and 13th week of age for post-weaning phase were lowly repeatable for female and heritable for male; indicating that additional records would be required to adequately characterize the inherent production ability of live body weight for dam and sire at pre and post weaning phases as breeding age progressed. It is therefore concluded that the low repeatability and heritability estimates recorded showed that collection of additional records and improvement of non-genetic factors influencing the growth traits would improve the accuracy of data for repeatability and heritability of growth trait of indigenous guinea pigs in Nigeria.